2020
DOI: 10.7150/thno.44419
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia induced exosomal circRNA promotes metastasis of Colorectal Cancer via targeting GEF-H1/RhoA axis

Abstract: Hypoxia is one of the important properties of solid tumor. However, oxygen supply within tumors is generally heterogeneous according to the distance from the nearest blood vessel. The discrepancy of metastatic potential exists between hypoxic cancer cells and relatively normoxic cancer cells. But the molecular mechanism remains poorly understood. Methods: Differential expression of circRNAs in plasma exosomes of CRC patients and normal subjects was performed by screening. Exosomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(98 citation statements)
references
References 36 publications
1
97
0
Order By: Relevance
“…Hypoxia is related to exosomes non-coding RNA. Previous studies reported that hypoxic BMSC-derived exosomal miRNAs promote metastasis of lung cancer cells 26 ; hypoxic cancer cell exosomal circ0048117 facilitates M2 macrophage polarization in esophageal squamous cell carcinoma 27 ; hypoxia-induced exosomal circRNA promotes metastasis of colorectal cancer via targeting GEF-H1/RhoA axis 28 ; hypoxia-associated circDENND2A promotes glioma aggressiveness by sponging miR-625-5p 29 . Our data demonstrated that circHIF1A from hypoxic CAFs exosomes promoted breast cancer stemness by regulating miR-580-5p targeting CD44 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is related to exosomes non-coding RNA. Previous studies reported that hypoxic BMSC-derived exosomal miRNAs promote metastasis of lung cancer cells 26 ; hypoxic cancer cell exosomal circ0048117 facilitates M2 macrophage polarization in esophageal squamous cell carcinoma 27 ; hypoxia-induced exosomal circRNA promotes metastasis of colorectal cancer via targeting GEF-H1/RhoA axis 28 ; hypoxia-associated circDENND2A promotes glioma aggressiveness by sponging miR-625-5p 29 . Our data demonstrated that circHIF1A from hypoxic CAFs exosomes promoted breast cancer stemness by regulating miR-580-5p targeting CD44 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al found that Hypoxia-derived exosomal circ-133 transported into normaxic cancer cells and promoted cell migration via miR-133a/GEF-H1/RhoA axis. This reveals a potential mechanism for that the intra-tumor heterogeneity of oxygen promote cancer progression 89 . In addition, hsa_circ_0004585, hsa_circRNA_102958, circRNA_101951, circ_0060745, circ_0001946, circRNA_0000392, and circRNA_100876 are highly expressed in CRC and regulate tumor growth through their own pathways.…”
Section: Circrna and Digestive System Neoplasmsmentioning
confidence: 90%
“…Circ-133 is associated with hypoxia and regulates the distribution of E-cadherin protein on the cell membrane. Then, it was verified in vivo and vitro that exosomal circ-133 from hypoxic cells were transported to normal oxygenated cells through miR-133a/GEF-H1/RhoA axis, which regulated the distribution of E-cadherin membrane and promoted tumor metastasis (Yang et al, 2020).…”
Section: Exosomal Circrnas May Be Therapeutic Targets For Inhibiting mentioning
confidence: 97%